1981
DOI: 10.1002/bjs.1800680421
|View full text |Cite
|
Sign up to set email alerts
|

The excretion of cefuroxime in human bile

Abstract: Cefuroxime is a broad spectrum cephalosporin antibiotic. An intravenous injection of cefuroxime 1.5 g was administered to 25 patients after induction of anaesthesia for cholecystectomy. Concentrations of antibiotic were measured and the mean levels in microgram/ml found to be: serum 120.5, common bile duct bile 42.8, gallbladder bile 5.4, gallbladder wall 39.2. The drug levels exceeded the minimum inhibitory concentrations for most organisms commonly encountered in the biliary tract. There was no difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

1983
1983
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
1
4
0
2
Order By: Relevance
“…Unfortunately, there are conflicting data on the efficacy of aminopenicillins and oral cephalosporins. Although studies support the use of cefuroxime (with metronidazole) given their excellent excretion into the biliary tract [ 24 ], we frequently cultured enterococci and unsusceptible Gram negative rods in our cultures, which is supported by other studies [ 8 ]. Therefore, cefuroxim can only be recommended in mild cases and based on local susceptibility rates which can be discussed with the local antibiotic stewardship team.…”
Section: Discussionsupporting
confidence: 73%
“…Unfortunately, there are conflicting data on the efficacy of aminopenicillins and oral cephalosporins. Although studies support the use of cefuroxime (with metronidazole) given their excellent excretion into the biliary tract [ 24 ], we frequently cultured enterococci and unsusceptible Gram negative rods in our cultures, which is supported by other studies [ 8 ]. Therefore, cefuroxim can only be recommended in mild cases and based on local susceptibility rates which can be discussed with the local antibiotic stewardship team.…”
Section: Discussionsupporting
confidence: 73%
“…1981 73 5.4 [G]/42.8 [BD]1500 mgivThomas et al . 1981 74 4.8 [G]/9.0 [BD]750 mgivSevern and Powis 1979 75 Cefpodoxime proxetil2.0–3.62080no data availableCefixime3.0–4.065501056.9 ± 70.9 [T]200 mgoralWestphal et al . 1993 76 199.3 (8.8–1163.8)200 mg twice daily (×4)oralMoorthi et al .…”
Section: Are All Cephalosporins the Same With Regard To CDI Risk?mentioning
confidence: 99%
“…However, this result has been controversial because another report showed that the interaction occurred in bile duct-cannulated rats (Yamamura et al, 1999). In addition, the biliary concentrations of carbapenems in human are less than those of other ␤-lactam antibiotics, which have been reported not to interact with VPA (Thomas et al, 1981;Shiramatsu et al, 1988;Morimoto et al, 1991;Granai et al, 1992;De Turck et al, 1998;Yamagata et al, 1998), supporting the fact that the interaction at the enterohepatic circulation process would be improbable in humans. As to the blood cell distribution process, Omoda et al (2005) reported that the blood levels of VPA were not changed when the plasma level was decreased after intravenous administration of VPA with carbapenems in rats.…”
Section: Discussionmentioning
confidence: 98%